A Web-based Model-driven Platform for Web Augmentation - Urbieta, Mario Matías (2019)
The emergence of Web personalization allowed introducing improvements to an application that runs as a black box just considering those perceivable behaviors by the end-user. In spite of which mechanisms (personalization, customization, etc.) that a particular application supports; it is not realistic to state that any application, being idealized by few people (e.g., its owners), covers every single user´s needs. In this sense, users may have unsatisfied requirements. Nowadays available Web augmentations are making full use of server-side capabilities for meeting requirements. We present a Web Augmentation modeling approach contemplating a client-server application that hides the back-end complexity to users. In this work we present a Web CASE tool to model server-side behavior for Web augmentation. This tool provides a full web-based experience for designing and running Web augmentations that requires client and server-side components.